(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The problem of individualization of the educational process with the introduction of inclusive practice in pre-school educational institutions, the inclusion of children with disabilities in general education is discussed, and the tasks that practitioners should address in accordance with the requirements of GEF preschool education: the readiness of teachers to solve problems Inclusion, provision of interaction between specialists of different profiles, inclusion of parents in an inclusive process, the construction of an educational process and taking into account special educational needs, individual opportunities, potential abilities of each child, monitoring the dynamics of children’s development are described. The importance of introducing a diagnosis of the individual dynamics of the development of a child with disabilities into the practice of preschool education, which opens up new opportunities in building an educational process that serves as a means to increase the effectiveness of the teacher and pre-school educational organization is emphasized. The conditions of a qualitative process of psychological and pedagogical support of children of preschool age with IDD are discussed on the basis of individualization of education in conditions of education.